THE INFLUENCE OF JOB SATISFACTION, ORGANIZATIONAL CULTURE, AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF LECTURERS AND EMPLOYEES AT STIESNU BENGKULU - Syafri Yanto; Ismi Azis; Resi Julita (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study aims to analyze the influence of job satisfaction, organizational culture, and organizational commitment on Organizational Citizenship Behavior (OCB) among lecturers and employees of STIESNU Bengkulu. Research Methodology: This research was conducted at the Nahdlatul Ulama Islamic Economics College (STIESNU) Bengkulu using a quantitative approach. Data collection was conducted through a survey using a questionnaire with a Likert scale. The research sample consisted of 46 respondents selected using a purposive sampling technique. Data analysis was performed using Statistical Product and Service Solution (SPSS) software version 26, through validity and reliability tests, classical assumptions, and multiple linear regression analysis. Results: The results of the study indicate that job satisfaction and organizational culture have a positive and significant effect on Organizational Citizenship Behavior (OCB). Meanwhile, organizational commitment has no significant effect and shows a negative relationship with OCB. Simultaneously, the variables of job satisfaction, organizational culture, and organizational commitment contribute 45.3% to the variation in OCB. Conclusions: Job satisfaction and organizational culture are important factors in increasing OCB behavior, while organizational commitment has not shown a significant role. Therefore, organizations need to focus more on improving job satisfaction and strengthening organizational culture to encourage positive work behavior. Limitations: This research is limited to a relatively small sample size and was only conducted at one institution, and only used a quantitative approach with limited variables. Contributions : This research contributes to the development of human resource management science, particularly in understanding the factors influencing Organizational Citizenship Behavior in higher education. Furthermore, the results of this study can serve as a reference for management in formulating policies to improve employee performance and behavior .